A patch to the possibility part of Gödel's Ontological Proof. (16th September 2019) - Gustafsson, Johan E
Abstract: Kurt Gödel's version of the Ontological Proof derives rather than assumes the crucial (yet controversial) Possibility Claim, that is, the claim that it is possible that something God-like exists. Gödel's derivation starts off with a proof of the Possible Instantiation of the Positive, that is, the principle that, if a property is positive, it is possible that there exists something that has that property. I argue that Gödel's proof of this principle relies on some implausible axiological assumptions. Nevertheless, I present a proof of the Possible Instantiation of the Positive, which only relies on plausible axiological principles. Nonetheless, Gödel's derivation of the Possibility Claim also needs a substantial axiological assumption, which is still open to doubt.